Enzalutamide: A Novel Anti-androgen with Prolonged Survival Rate in CRPC Patients - Dhingra, Richa; Sharma, Tina; Singh, Sukhminder; Sharma, Shivani; Tomar, Prince; Malhotra, Manav; Bhardwaj, T.R. (Mini Reviews in Medicinal Chemistry, 2013)
Prostate cancer is the most common malignancy among men found to be the second leading cause of male cancer-related mortality due to development of resistance against androgen deprivation therapy (ADT). With the advancement in understanding of prostate cancer, numbers of agents have been emerged to target Androgen-Receptor (AR) signaling for the treatment of castration resistant prostate cancer (CRPC). Food and Drug Administration (FDA) has recently approved enzalutamide (XTANDI) for the treatment of CRPC. Androgen receptor promotes the prostate cancer progression after transformation. Androgen receptor signaling leads to CRPC when cellular nucleus binds to DNA and increases pro cancer gene expression. In phase ΙΙΙ clinical trial, enzalutamide showed that 160 mg once daily oral administration is well tolerated and significantly enhanced overall survival in men with CRPC after chemotherapy, demonstrated by reduction in the serum prostate specific antigen (PSA) level and increased survival rate by 4.8 months.
Keywords: Castration resistant prostate cancer (CRPC)